Response of Microtermes mycophagus (Isoptera: Termitidae) to twenty one wood species - Naeem Iqbal; Hafiz Azhar Ali Khan; Shafqat Saeed (PeerJ, 2015)
The responses of termite species to bait depend upon the quality of the food used in the stations. Woods are the most common food sources for termites but different termite species behave differently to different wood species and types. The knowledge of the preference status of different wood species to a termite species helps in effective monitoring and baiting program. The current study was carried out to evaluate the preference of 21 wood species to the termite, Microtermes mycophagus in the field by no-choice and choice feeding tests. The results indicated silk cotton tree and sacred fig woods as the most preferred wood species with mean mass losses of 71.21 ± 5.09% and 68.38 ± 7.27% in no-choice test and 95.02 ± 1.65% and 91.69 ± 2.07% in choice tests, respectively. White cedar was the least preferred wood species with mean mass losses of 7.49 ± 1.64% and 13.92 ± 1.89% in no choice and choice feeding tests, respectively. Based on present studies, sapwood of silk cotton tree and sacred fig may be used in effective monitoring and baiting program against M. mycophagus.